1996
DOI: 10.1103/physrevlett.77.703
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy in the Adsorption ofH2O at Low Coordination Sites on Pt(111)

Abstract: The H 2 O adsorption on Pt(111) at 140 K is investigated by temperature-variable scanning tunneling microscopy. H 2 O adsorbs preferentially at the upper side of step edges. At these low coordination sites the adsorbates are bound stable as quasi-one-dimensional chains up to 160 K. In contrast, the desorption from the two-dimensional H 2 O islands on the terrace has already started at 145 K. The occupancy of the sites at the upper side of step edges is different at the two types of dense packed steps. This ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
148
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(169 citation statements)
references
References 17 publications
19
148
1
1
Order By: Relevance
“…Using a temperature programmed desorption (TPD) and spectroscopic methods (XPS, UPS), Sexton and Hughes, obtained the adsorption energy of water on Pt(111) is 0.412 eV [48]. However, for the case of (111) surface index, our result of the atop position as the most preferential adsorption site is in agreement with STM results by Morgenstern et al [23,49]. The weakest interaction strength of H2O/Pt(111) compared to Pt(100) and Pt(110) indicates the most unflavored water dissociation at the Pt(111) surface.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Using a temperature programmed desorption (TPD) and spectroscopic methods (XPS, UPS), Sexton and Hughes, obtained the adsorption energy of water on Pt(111) is 0.412 eV [48]. However, for the case of (111) surface index, our result of the atop position as the most preferential adsorption site is in agreement with STM results by Morgenstern et al [23,49]. The weakest interaction strength of H2O/Pt(111) compared to Pt(100) and Pt(110) indicates the most unflavored water dissociation at the Pt(111) surface.…”
Section: Resultssupporting
confidence: 81%
“…While the mechanism of adsorption of methanol and its derived fragments on Pt and Pt alloy surfaces was explained in our earlier work [17][18][19][20], we now come to H2O-Pt systems. In this case, the existence of H2O molecules on Pt surfaces was confirmed by several experiments using different techniques, such as atom superposition and electron delocalization (ASED) [21], low energy electron diffraction (LEED) [22], or scanning tunneling microscopy (STM) [23]. Theoretical studies have also extended the investigation of water at various Pt-surface models in order to obtain the fundamental correlation between surface geometry and electronic structure and reactivity [24][25][26][27].…”
Section: Introductionmentioning
confidence: 91%
“…Our data neither rule out nor corroborate the hypothesis that PtRu interfaces are the most catalytic ones, but they convincingly show that PtRusteps and remaining Ptsteps are little catalytic active for CO oxidation ( Figures 5 and 7 Figures 6B and 7B). Indeed, from solid/gas interface studies, [72][73][74] it is well known that water adsorption and its dissociation preferentially occur in the upper parts of step edges compared to closepacked domains. In this respect, once the adsorbates strongly adsorb at the steps, this could at least partially explain the higher over-potentials required for the reaction Ptκ Figure 4 evidence that after partial oxidation of a CO adlayer, on a Ru partially modified Pt step, the sites released in the first voltammetric cycles apparently were not reoccupied by the remaining CO molecules on surface.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…11 There is evidence that water molecules preferentially bind to steps on Pt(111). On one hand, STM measurements 20 show that annealing (2 min at 160 K) of a monolayer desorbs all water except chains along both types of densely packed steps (steps in the 〈11 j 0〉 direction with either (100) microfacets (also called A-steps) or (111) microfacets (B-steps), see Figure 1). Density functional theory (DFT) calculations indicate that water molecules form one-dimensional, hydrogen bonded chains along step edges.…”
mentioning
confidence: 99%
“…23 A few earlier studies reported additional signals in the TDS for higher temperatures; namely, a peak/shoulder at T ≈ 198 K, 24,25 which has been tentatively assigned to desorption from step edges. 20 This issue was clarified by a study on a vicinal Pt(335) surface, which clearly revealed a peak at T ) 198 K due to molecules bound to step edges in addition to the multilayer (T ) 160 K) and monolayer peak (T ) 185 K). 21 A further source for additional high temperature desorption peaks is the presence of OH, which tends to stabilized, mixed OH-H 2 O overlayer on Pt(111).…”
mentioning
confidence: 99%